Web Based Studio Management System for Studios and Color Labs - Weerasekara B.J.D.A; Ayuwardhana H.M.K.J.J; Rodrigo P.H.M.S; Roshani O.V.D.E; De Silva D.I; Samarasekara H.M.P.P.K.H (International Journal of Engineering and Management Research, 2022)
Simple interfaces are provided by studio management systems for maintaining studio data. It is possible to run a studio effectively with this studio management system. Also, there is the ability to securely store the data of the customers who come to the institution. Also, this data can be updated and deleted at any time. Additionally, it includes the customer's name, phone number, order type, dates, instructions for the required pictures and videos, as well as details on the pertinent occasions and dates. The information about the amounts paid and the relevant dates from the day the customer gave the advance is stored in this system. Orders are separated into pieces and processed gradually in accordance with the orders placed by the respective consumers. Also, this system has been set up in such a way that customers can get a bill with the amount spent after providing the required data. The main aim of introducing a computerized system for studio management is to increase the effectiveness and overcome the drawbacks of a manual system.